#1**+1 **

Solve for x:

x^3 + 2 x^2 - 11 x - 12 = 0

Factor the left hand side.

The left hand side factors into a product with three terms:

(x - 3) (x + 1) (x + 4) = 0

Find the roots of each term in the product separately.

Split into three equations:

x - 3 = 0 or x + 1 = 0 or x + 4 = 0

Look at the first equation: Solve for x.

Add 3 to both sides:

x = 3 or x + 1 = 0 or x + 4 = 0

Look at the second equation: Solve for x.

Subtract 1 from both sides:

x = 3 or x = -1 or x + 4 = 0

Look at the third equation: Solve for x.

Subtract 4 from both sides:

**x = 3 or x = -1 or x = -4**

Guest Dec 30, 2017

#2**+2 **

x^3+2x^2-11x-12 = 0 we can write this as

x^3 + x^2 + x^2 - 11x - 12 = 0 factor

x^2(x + 1) + ( x - 12) ( x + 1) = 0

(x + 1) ( x^2 + x - 12) = 0

(x + 1) ( x + 4) ( x - 3) = 0

Setting each factor to 0 and solving for x gives the roots

x = -4, x = -1 and x = 3

And their sum is -2

CPhill
Dec 30, 2017